Finite element mapping for incompatible FE meshes of composite structures. (September 2016) - Mayer, Natalie; Van Den Broucke, Björn; Prowe, Jens; Havar, Tamas; Hinterhölzl, Roland
Highlights: A FE mapping algorithm for a data transfer between incompatible meshes is proposed. The structural analysis is based on process simulation data for composites. Only the transfer of fiber orientations is not sufficient for a structural analysis. Material properties such as FVC, permeability and stiffness are predicted. The method is capable of handling partially out-of-plane wrinkling defects. Abstract: Finite element analysis (FEA) of structural composites is mostly based on an as-designed geometry and input data. As-designed input data do not consider the manufacturing processes. For an as-built structural simulation of composites, it is important to integrate manufacturing process data into the structural analysis. Therefore, mapping algorithms are needed to transfer and process data between different process and structural simulation steps considering the application of different finite elements and media discretization for the individual simulation steps. This paper considers a mapping algorithm based on a bucket sort algorithm, shape interpolation functions of finite elements and internal fiber architectures of composite materials with a subsequent material properties prediction. The proposed algorithm is applicable for unidirectional composites as well as for non-crimped, woven and braided fabrics. Particular, it is shown how fiber orientation, as vector value of finite elements, is sensible for a data transfer between meshes with out-of-plane material defects. This integrated simulation approach is applied on a generic demonstrator geometry and aerospace component geometries. The implementation is realized within a new developed simulation platform for composites structures, from process up to structural simulations.